Gestational Hydronephrosis: A Retrospective Analysis of the Clinical Outcomes of Ureteral Stent Placement Versus Conservative Treatment - Dursun Baba; Engin Yurtçu; Burak Ayvacık; Yusuf Salih Küçük; Arda Taşkın Taşkıran; Mehmet Ali Özel; Ahmet Yıldırım Balık; Ekrem Başaran; Betül Keyif (Medicina)
Background and Objectives: Gestational hydronephrosis (GH) is a physiological condition commonly observed during pregnancy, resulting from hormonal effects and mechanical compression of the ureters by the enlarging uterus. Although often asymptomatic, GH can cause urinary stasis, recurrent infections, and renal function impairment in symptomatic cases. The optimal management of such cases remains controversial, especially regarding the role of ureteral stent placement. This study aimed to compare clinical outcomes—including renal function, inflammatory markers, and obstetric parameters—in pregnant women with symptomatic GH who underwent ureteral stent placement versus those managed conservatively. Materials and Methods: We conducted a retrospective cohort study at Düzce University Hospital between 2020 and 2024, including 40 pregnant women diagnosed with symptomatic GH. The patients were divided into the following two groups: those who received a ureteral stent (n = 20) and those who were managed with conservative treatment (n = 20). Conservative management included hydration therapy, acetaminophen-based analgesia, and close clinical monitoring. The parameters assessed included serum creatinine, estimated glomerular filtration rate (GFR), inflammatory markers (C-reactive protein, erythrocyte sedimentation rate, and white blood cell count), urinary findings, obstetric outcomes, and postpartum complications. Statistical significance was set at p < 0.05. Results: Gestational age at diagnosis was significantly higher in the stent group (29.1 ± 3.2 weeks) than in the non-stent group (27.1 ± 3.5 weeks; p = 0.045), possibly reflecting increased mechanical compression in later pregnancy. Renal function parameters (serum creatinine and GFR), inflammatory markers (CRP, ESR, and WBC count), and obstetric outcomes (birth weight, Apgar scores) showed no significant differences between groups (p > 0.05). Interestingly, gestational diabetes mellitus (GDM) was more prevalent in the non-stent group (20% vs. 5%; p = 0.042), although no significant differences were found in fasting glucose levels. Conclusions: Ureteral stent placement in symptomatic GH does not appear to significantly improve renal function or obstetric outcomes. However, it may provide symptom relief in select patients with persistent or severe discomfort. Given the limitations of retrospective data and a small sample size, further prospective studies with larger cohorts and quality-of-life assessments are warranted to optimize management strategies and enhance patient-centered care.